AB0305 Potential in vitro immunomodulatory effects of the recombinant human alpha-enolase on peripheral blood mononuclear cells (pbmcs) from healthy donors. (23rd January 2014) - Guillou, C.; Avenel, G.; Derambure, C.; Verdet, M.; Golinski, M.-L.; Hiron, M.; Adriouch, S.; Boyer, O.; Lequerré, T.; Vittecoq, O.
Abstract : Background: Identification of autoantibodies associated with rheumatoid arthritis has been of major interest. In this context, we have previously identified for the first time α-enolase (ENO) as a new auto-antigen in early RA. ENO is an evolutionary conserved protein involved both in glycolysis pathway and as a plasminogen receptor which confer it a role in anti-infectious inflammatory response. In vivo, preliminary studies showed that ENO had immunomodulatory effect in the collagen induced arthritis mouse model 1 . Objectives: To better understand the immunological mechanisms of ENO, the aim of this in vitro study was to determine the effects of ENO on PBMCs from healthy donors. Methods: : In one hand, PBMCs or different cell types (monocytes, B and T cells, and immature dendritic cells [iDC]) (n=3) were cultured with ENO (20 µg/mL) or Bovine Serum Albumin (20 µg/mL). TNFα and IL-10 production was measured in the supernatants by ELISA at different times. On the other hand, TNFα and IL-10 production were evaluated in PBMCs, monocytes or B and T cells after LPS stimulation and pre-incubation with ENO for 24h (n=3). Cytometric analyses have evaluated the ability of ENO to inhibit the differentiation of monocytes into iDC or iDC into mature DC. Before differentiation into iDC (GM-CSF and IL-4), monocytes (1.106cells/mL) were incubated with ENO (20 or 50µg/mL) for 24h. Results: In cultures of PBMCs, monocytes or iDC, ENO induces, dose dependently, an early production of TNFα followed by extended secretion of IL-10. PBMCs or individual cells (monocytes, B and T cells) stimulated by LPS secreted successively TNFα and IL-10, while PBMCs or individual cells, stimulated by LPS but previously incubated with ENO for 24h did not secrete these cytokines. In contrast to LPS, ENO did not induce differentiation of immature dendritic cells into mature cells. Moreover, ENO has the capacity to inhibit differentiation from monocytes to iDC. Conclusions: This study suggests that ENO has no pro-inflammatory effect unlike LPS. Indeed, ENO might have immunomodulatory properties via IL-10 production. Others studies focused on an extended cytokine panel and different signaling pathways are underway to better understand the immunological mechanisms induced by ENO. References: C. GUILLOU et al., Arthritis and Rheumatism 2011, 63:S815. Disclosure of Interest: None Declared